Non‐thermal atmospheric plasma treatment of onychomycosis in an in vitro human nail model. Issue 2 (15th December 2019) - Bulson, Jeffry M.; Liveris, Dionysios; Derkatch, Irina; Friedman, Gary; Geliebter, Jan; Park, Sin; Singh, Sarnath; Zemel, Marc; Tiwari, Raj K.
Summary: Background: Onychomycosis affects almost 6% of the world population. Topical azoles and systemic antifungal agents are of low efficacy and can have undesirable side effects. An effective, non‐invasive therapy for onychomycosis is an unmet clinical need. Objective: Determine the efficacy threshold of non‐thermal atmospheric plasma (NTAP) to treat onychomycosis in an in vitro model. Methods: A novel toe/nail‐plate model using cadaver nails and agarose media inoculated with Candida albicans was exposed to a range of NTAP doses. Results: Direct exposure of C albicans and Trichophyton mentagrophytes to 12 minutes of NTAP results in complete killing at doses of 39 and 15 kPulses, respectively. Onset of reduced viability of C albicans to NTAP treatment through the nail plate occurs at 64 kPulses with 10× and 100× reduction at 212 and 550 kPulses, respectively. Conclusions: NTAP is an effective, non‐invasive therapeutic approach to onychomycosis that should be evaluated in a clinical setting.